KEMITRAAN ANTARA PEMERINTAH KOTA DENGAN SWASTA DALAM PEMBANGUNAN DAERAH DI KALIMANTAN - PKP2A III LAN Samarinda, Tim Kajian (Jurnal Borneo Administrator, 2009)
Mutual partnership between government and private sector or Public Private Partnership (PPP/P3s) is purposed to overcome government’s limited resources in doing regional development and public service. The advantages of partnership implementation are participation, regional income, public service improvement and absorbtion of manpower. The practices of PPP/P3s in Kalimantan have produced several kinds of partnership varians. However they’re still done in goods and service group only, and several of them tend to profit oriented. There isn’t any breakthrough of partnership on administratif services done by regional goverments. Some problems in PPP/P3 practices are negatif stigma toward government aparatus, insfrastructure facilities, government regulation and aparatus perception on partnership. District/city governments should make inovative breakthroughs to implement the partnership with private sector in all services group.  Keywords: public private partnership, public service, regional development